The relationship between drug therapy adherence and the results of blood pressure targets achievement in hypertensive patients with dyslipidemia complications at Government Hospital in Yogyakarta - Andriana Sari; Faridah Baroroh; Fitriani Puji Astuti (Pharmaciana, 2020)
Hypertension is a chronic disease that affects most people. Almost every people have certain specific factors that can cause this disease to increase. One of which is inadequate physical activity so that cholesterol levels remain and tend to get higher, which is a risk factor for heart and blood vessel disorders. Patients with this disease and having dyslipidemia complications must treat with appropriate therapy until reaching success. The patient's adherence determines the success of the treatment. Therefore the purpose of this research is to assess the relationship. Its objects were hypertensive patients at the Government Hospital in Yogyakarta. The specialty of the hypertensive patient is having dyslipidemia complications. The study uses non-experimental with a cross-sectional study. The sample was selected based on the purposive sampling technique in December 2018-February 2019. The measurement of therapy adherence used MARS questionnaire and the achievement of therapy targets through secondary data on patient blood pressure. Chi-square test was chosen to determine the relationship between 2 variables, which are therapy adherence and achieving blood pressure targets. The sample in this study were 47 respondents, of which 53.2% of the patients were <60 years old, in which 51.1% of them were female. The results showed that patients who were adherent to therapy were 25.5%, and those who were not were 74.5%. The results of achieving the blood pressure target are known to be 68.1%. The data analysis results showed that the one-way hypothesis in Fisher's test obtaining p-value = 0.171 (p> 0.05) was no relationship between adherence and target achievement. Therefore the results of this study concluded that there is no relationship between drug therapy adherence and blood pressure targets achievement.